Qualitative and Quantitative Aspects of the Human Antibody Response to Streptococcal Group A Carbohydrate - Shulman, Stanford T. (1974)
The lack of impressive quantitative differences in antibody to various streptococcal extracellular and cellular antigens among patients with acute rheumatic fever, acute glomerulonephritis, and following uncomplicated streptococcal infection has prompted investigation of qualitative aspects of the antibody response among these patients. By using a radiolabeled antigenically univalent hapten derived from streptococcal A carbohydrate, affinity of serum antibody to A-carbohydrate (A-antibody) was studied by an ammonium sulfate precipitation technique. The data obtained demonstrate average association constants (K0S) of acute rheumatic fever patient sera to be significantly lower than those of acute glomerulonephritis or streptococcal infection patients (P<0.02 and P<0.001, respectively). Further analysis of the data from hapten binding studies documents the fact that the radioimmune precipitin assay for the determination of A-antibody level is little influenced by K0 but directly correlates with the concentration of antibody binding sites. These data suggest that qualitative differences in A-antibody are present between rheumatic and non-rheumatic individuals. It is unclear whether the finding of low-affinity A-antibody among acute rheumatic fever patients reflects a generalized phenomenon or one restricted to the A-antibody-A-carbohydrate system.